Study of Mitogenomes Provides Implications for the Phylogenetics and Evolution of the Infraorder Muscomorpha in Diptera - Huan Yuan; Wenbo Fu; Shulin He; Tingjing Li; Bin Chen (Ecology and Evolution, 2025)
ABSTRACT The Muscomorpha is one of the most species‐rich brachyceran groups in Diptera, with many species serving as important disease vectors; however, its high‐level phylogenetic relationships have long been controversial and unsolved. This study comparatively analyzed the characteristics of mitogenomes of 131 species that represent 18 superfamilies in Muscomorpha, in which mitogenomes of 16 species have been newly sequenced and annotated, demonstrating that their gene composition, order, AT bias, length variation, and codon usage are consistent with documented dipteran mitogenomes. The phylogenetic topologies demonstrated that the robustness of Muscomorpha and major clades within Muscomorpha are monophyletic: Cyclorrhapha, Schizophora, and Calyptratae. A clade of Empidoidea were recovered as the sister group to Cyclorrhapha. Within Cyclorrhapha, Platypezoidea and Syrphoidea were sequentially placed as basal groups of the Cyclorrhapha. The remaining cyclorrhaph superfamilies gathered as two main clades. Ephydroidea were, in most cases, placed as the sister group to Calyptratae. Within Calyptratae, Hippoboscoidea were sister to an assemblage of lineages composed of an Oestroid grade and Muscoidea. The Muscomorpha was proposed to originate in the early Jurassic, and the main clade diversified near the Cretaceous–Paleogene extinction event, estimated using the MCMCtree and six fossil calibration points. The ancestral area of origin and geographic range of Muscomorpha was deduced to be the Palaearctic region with 56.9% probability using the RASP software based on a dated tree.